A REVIEW OF LABORATORY STUDIES OF ADULT SECOND LANGUAGE VOCABULARY TRAINING. Issue 2 (May 2020) - Rice, Caitlin A.; Tokowicz, Natasha
Abstract: This review examines and integrates studies of second language (L2) vocabulary instruction with adult learners in a laboratory setting, using a framework provided by a modified version of the Revised Hierarchical Model (Kroll & Stewart, 1994), the Revised Hierarchical Model-Repetition Elaboration Retrieval. By examining how various training methods promote or fail to promote the development of high-quality orthographic, phonological, and meaning representations, and strong connections between these representations, we reconceptualize the current body of knowledge, and highlight gaps in the existing literature. We review evidence that training methods that only promote L1 to L2 form connections (e.g., massed repetition) are generally ineffective, but can become highly effective when paired with methods that also strengthen L2 form-meaning connections (e.g., spaced repetition training with retrieval practice or semantic elaboration requiring user-generated responses). We discuss the implications of these findings for researchers and educators interested in improving L2 vocabulary learning outcomes.